Preferred functionalization of metallic and small-diameter single walled carbon nanotubes via reductive alkylation - Wunderlich, David; Hauke, Frank; Hirsch, Andreas (Journal of Materials Chemistry, 2008)
A selectivity investigation of the covalent sidewall functionalization of SWNTs by reductive alkylation (Billups reaction) is reported. The functionalized tubes R-SWNT were characterized by UV-vis-nIR absorption, nIR emission and Raman spectroscopy. The reduction of SWNTs with sodium and the subsequent alkylation of the reduced tubes SWNT with butyl iodide reveal a pronounced SWCNT diameter dependence, that is, SWNTs with smaller diameter are considerably more reactive than tubes with larger diameter. Moreover, this reaction sequence also favours the preferred functionalization of metallic over semiconducting tubes. Treatment of the reduced intermediates SWNT with protons, via the use of ethanol, instead of alkyl iodide leads to hydrogenated tubes. However, in this case the degree of functionalization is considerably lower than that observed for the corresponding alkylation. Also no pronounced preference of the reaction of metallic and small diameter tubes was observed during the hydrogenation process. © The Royal Society of Chemistry.